Probiotic Potential Test for Lactic Acid Bacterial Isolate from Labi Cattle Gastric Again Low Acidity and Sodium Deoxycholate - Sanjaya, I Made Rahma; Suardana, I Wayan; Suarsana, I Nyoman (Journal of Veterinary and Animal Sciences, 2019)
Lactic acid bacteria (LAB) are one of group probiotic bacteria, which have a positive impact on human and animal health. The aim of this research was to determine the potency lactic acid bacterial isolate from LABi cattle gastric as a probiotic that have resistance to low pH and sodium deoxycholate. The study was started with the cultivation test that aims to made sure uncontaminated isolates of microorganisms, including test for growth response in MRS broth medium, test on catalase production, and Gram stain. Its potency for probiotic development was tested by growing of isolate in MRS broth medium with low pH conditions (pH 2, 3, 4) and in MRS medium supplemented with various concentration of sodium deoxycholate (0,2 mM, 0,4 mM, 0,6 mM). The result showed that isolate from LABi cattle gastric was able to grow well in MRS broth medium under anaerobic condition. In addition, it also showed catalase negative and Gram-positive bacteria. In the main experiment, this isolate was found to be resistant to low pH conditions (up to pH 2) and high concentration of sodium deoxycholate (up to 0,6 mM). These results indicate that the isolate the lactic acid bacteria have resistance to low pH and the sodium deoxycholate, which is the main requirement of the probiotic bacteria